EVALUASI KINERJA JARINGAN PIPA TRANSMISI MATA AIR PEBINI KECAMATAN KINTAMANI KABUPATEN BANGLI - SORIARTA, KETUT; ARDANA, PUTU DODDY HEKA; CAHYA, M. ALDI (Universitas Mahasaraswati K. Mataram, 2023)
The existing transmission pipeline network in Kintamani District, especially in the RV-II Reservoir in Catur Village to the RV-III Reservoir in Belantih Village, often experiences disruption due to leaks. The existing transmission pipe has a diameter of 12 inches and is of the Poly Vinyl Chloride (PVC) type. The current condition of the existing transmission pipe has been repaired several times due to leakage problems and the age of the pipe can be categorized as old. This research is to determine the condition of the existing transmission pipe network and find solutions to overcome problems in the leaking transmission pipe network. So that the water discharge pumped to RV-III Belantih Village can be maintained at 60 l/sec. Hydraulic analysis of pipe networks using the Epanet program. Based on primary data, the total pipe length from RV-II Catur Village to RV-III Belantih Village is 5,050 m. However, the plan to replace the existing transmission pipe is only 1,200 m long. Based on the results of the analysis of population growth in Catur Village and Belantih Village, the calculation results show that it is 0.0127% per year. The service distribution network to Catur Village and Belantih Village of 18.75 l/s is only able to meet the population's water needs until 2036. Simulation using the Epanet program, at nodes RP2.16 to RP2.40, the Ø10 inch PVC pipe design has a maximum pressure of 8,857 bar while the existing Ø12 inch PVC pipe has a maximum pressure of 9.3 bar. The simulated flow discharge for 24 hours is constant at 60 l/s resulting in a flow velocity of 1.22 m/s. Replacing pipes using Ø 10 inch PVC pipes is safer and more cost effective.